User-centered design for additive manufacturing as a customization strategy - Chua, Zhong Yang (2016)
As additive manufacturing (AM) has broadened design freedom significantly, conventional design theories and methodologies for customization or mass customization are challenged. This research aims at developing a user-centered design methodology for additively manufactured interactive parts that improves the level of customization. We propose a design methodology built upon the concepts of the three link chain model-based design for AM and design for customization. The proposed methodology also utilizes affordance- and preference-based finite state automata model to reflect preferable behavioral design requirements for customization in a dynamic artifact-user interaction context. The methodology deals with the design complexity increased by exploring AM-enabled design freedom in a systematic engineering design approach. Then this paper discusses the methodology’s availability in the design of additive manufactured interactive products such as prosthetic limbs.